2015
DOI: 10.1016/j.molimm.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FcRn for the modulation of antibody dynamics

Abstract: The MHC Class I-related receptor, FcRn, is a multitasking protein that transports its IgG ligand within and across cells of diverse origins. The role of this receptor as a global regulator of IgG homeostasis and transport, combined with knowledge of the molecular details of FcRn-IgG interactions, has led to opportunities to modulate the in vivo dynamics of antibodies and their antigens through protein engineering. Consequently, the generation of half-life extended antibodies has shown a rapid expansion over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 147 publications
(296 reference statements)
2
60
0
Order By: Relevance
“…Finally, differences might already occur during endocytosis via non-specific fluid-phase pinocytosis and intracellular sorting by separate recycling pathways. 21,[26][27][28] In summary, our results further underline the unique pharmacokinetic properties of IgG in comparison to different Fc fusion proteins comprising an identical Fc region and also identical variable domains, and for some of the molecules that are also similar in size. Differences in dissociation from bound FcRn at neutral pH can be correlated with a reduced half-life.…”
Section: Discussionsupporting
confidence: 59%
“…Finally, differences might already occur during endocytosis via non-specific fluid-phase pinocytosis and intracellular sorting by separate recycling pathways. 21,[26][27][28] In summary, our results further underline the unique pharmacokinetic properties of IgG in comparison to different Fc fusion proteins comprising an identical Fc region and also identical variable domains, and for some of the molecules that are also similar in size. Differences in dissociation from bound FcRn at neutral pH can be correlated with a reduced half-life.…”
Section: Discussionsupporting
confidence: 59%
“…Swiercz et al showed that an injection of Abdegs 8 hours after administration of 124 I-pertuzumab decreased background and improved tumor-to-blood ratios. The authors also note that the faster clearance time of the labeled probe decreased the levels of radioactivity exposure, an important consideration in clinical practice (Swiercz et al, 2014; Ward et al, 2015). …”
Section: Development Of Antibodies and Fragments For In Vivo Imagingmentioning
confidence: 99%
“…The molecular weight of 150 kDa exceeds the renal clearance threshold of 70 kDa and prevents the protein from being eliminated via the kidney. Additionally, the interaction with the neonatal Fc receptor leads to a continuous recycling process [29].…”
Section: Immunocytokine Formats and Target Antigensmentioning
confidence: 99%